2021
DOI: 10.1007/s11056-021-09893-8
|View full text |Cite
|
Sign up to set email alerts
|

Local-scale dispersal patterns and susceptibility to Dryocosmus kuriphilus in different Castanea species and hybrid clones: insights from a field trial

Abstract: The chestnut gall wasp Dryocosmus kuriphilus is a major insect pest affecting chestnut trees worldwide. Medium and long-term control of this pest can be improved by using resistant or less susceptible cultivars and hybrid clones. In addition, little is known about the local patterns of dispersal of the pest. We obtained data from trees of 3 chestnut species and 27 hybrid clones in a field trial in NW Spain with the aim of evaluating the susceptibility of the material to the gall wasp and identifying possible d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…(UTM Coordinates: 587161 m E, 4786989 m N; ETRS89 H29T). The trial was established in spring 2004 to test certain traits of interest in the Galician breeding program for hybrid chestnut clones (Castedo-Dorado et al, 2021). Dryocosmus kuriphilus colonized the planting in 2015, which coincides with the beginning of our study.…”
Section: Field Trial and Experimental Designmentioning
confidence: 99%
See 4 more Smart Citations
“…(UTM Coordinates: 587161 m E, 4786989 m N; ETRS89 H29T). The trial was established in spring 2004 to test certain traits of interest in the Galician breeding program for hybrid chestnut clones (Castedo-Dorado et al, 2021). Dryocosmus kuriphilus colonized the planting in 2015, which coincides with the beginning of our study.…”
Section: Field Trial and Experimental Designmentioning
confidence: 99%
“…We selected the four shady replicates for this study, to minimize variation due to topography and geographic orientation (Figure 1). The different genotypes showed high variability in susceptibility to D. kuriphilus, with seven clones showing total resistance after 4 years of attack (i.e., no galls in the crown in mid-summer) while others showed medium or high attack levels (see Castedo-Dorado et al, 2021). However, when visiting the trial in spring to collect leaves for other studies, we observed that some of these resistant clones showed small galls in leaves that, somehow, disappeared later (Figure 2).…”
Section: Field Trial and Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations